Wyłączenie bezprawności rozpowszechniania wizerunku osób powszechnie znanych w materiale prasowym - Nowikowska, Monika (Studia Prawnoustrojowe, 2019)
The article presents the problem of image protection of public figures in media. The purpose of the article is to provide in-depth reflection of emphasis and importance of protec-tion of image of public figures. On the other hand, the role of media in free communication needs to be recognized. The article is divided into two parts. In first part of article author focuses on analysis of the concept, and the legislative use of image. Starting with the definition and the scope of right to image, it will then look at the way in which the aspects of right to image developed. The article presents various defini-tions of image. The second part presents the problem of media publication of image. The article has been written on the basic of scientific literature concerning the activity of the media using image of public figures. The article is preliminary to the future research in this domain.